Nitrificação e desnitrificação de efluentes líquidos - Rocha, Renata Ribeiro de Araújo (1997)
In the biological treatment of wastewaters, there are interactions of several mechanisms, some of them happen simultaneously and others in series. In the present work, the system of biological treatment was based on the oxidation of organic and nitrogen matter (N-NH4+) of synthetic effluent simulating domestic waste. For the nitrogen matter removal, the nitrification and denitrification processes were used, in series. The study was developed under continuous system and the performance of the nitrification and denitrification processes was evaluated, as well as, the organic matter removal during the three experiments. In the curse of the three experiments, the performance of the nitrification process was evaluated using a three-phase fuidized bed bioreactor. The support used for the development of the biofilm was cylindrical PVC particles, with specific mass of 1,37g/cm3, equivalent diameter of 2,94mm and spherecity of 0,81. For the experiment 1, the three-phase fluidized bed bioreactor (nitrification) operated with 1-hour-hydraulic retention time. For the denitrification tank the hydraulic retention time was 5 hours. Dissolved oxygen and pH was monitored during the nitrification. The synthetic effluent used along this experiment provided concentrations of 180 - 200 mg/L of COD, 25 - 30 mg/L of N-NH4+ and 6 - 8 mg/L of total phosphorous. In the course of experiment 2 the fluidized bed operated with hydraulic retention time of 1 and 4 hours; the denitrification tank operated with hydraulic retention time of 5 and 20 hours. The synthetic effluent used for this experiment provided concentrations of 180 - 230 mg/L, 25 - 54 mg/L of N-NH4+ and 12 - 13 mg/L of total phosphorous, and macronutrients was added for the good performance of the microorganisms. Dissolved oxygen, pH and temperature was monitored for the nitrification process. During the third experiment, the three-phase fluidized bed bioreactor operated with 4-hour hydraulic retention time. For the denitrification, a completely mixed reactor was used with hydraulic retention time of 4 hours and 33 minutes. The synthetic effluent used for this experiment was similar to experiment 2, save for the concentration of N-NH4+ that was 25 - 30 mg/L. For the nitrification process, pH and dissolved oxygen was monitored. For the denitrification process, only dissolved oxygen and extra carbon source quantity were monitored, which provided concentrations of 41 - 292 mg/L of DQO for the process. The ammonium, nitrite and nitrate content, and protein and polysacharides content attached to the support (fluidized bed) were accomplished in the course of all experiments to attend and evaluation of the processes. The results indicated that the nitrification process was efficient only for 4-hour hydraulic retention time, reaching efficiencies of about 100%. The best results related to the efficiency of the denitrification process was obtained when the carbon source was supplemented to the process, reaching efficiencies of nitrite and nitrate removal of about 100%. The increment of hydraulic retention time in the course of the experiments don't end in better results of DQO removal. The results indicated efficiency of DQO removal of 86,32% to 97,99%.